Trust and technology in B2B e-commerce : practices and strategies for assurance - Kumar, Muneesh; Sareen, Mamta, 1968- (Business Science Reference, 2012)
"This book focuses on various trust issues that emerge from deployment of various e-commerce technologies in inter-organizational relationships, including security, privacy, authentication, non-repudiation, quality of web interface, system performance and infrastructure, environmental factors"--Anotace od vydavatele
Keywords: elektronický obchod; electronic commerce; příručky; handbooks, manuals, etc